2020
DOI: 10.1002/eat.23245
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fracture risk in women with eating disorders: The utility of dual‐energy x‐ray absorptiometry (DXA)—Clinical cohort study

Abstract: Objective: Eating disorders (EDs) are associated with decreased bone mineral density (BMD) and increased fracture risk. The association between BMD and fracture risk in EDs is not well elucidated. We aimed to assess BMD in an ED cohort of patients with active disease and patients in remission, and to assess the predictive value of BMD on incidence of fractures. Method:We included 344 female patients (median age 19, IQR 16; 24) referred to ED treatment. Later, patients were invited to follow-up including assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
6
1
Order By: Relevance
“…Another aspect that must be kept in mind is that eating disorders are related to fractures in adolescents, especially in girls, and T1D is known to be associated with disturbed eating behavior. (39,40) Even in our cohort, the proportion with fractures, with versus without eating disorders, was 60 (38 to 79) % versus 16 (14 to 18) %, p < 0.001 in females, whereas no significant difference could be found in males (31 [12 to 59] % versus 17 [15 to 18] %, p = 0.183). However, these results should be interpreted with caution as only 33 (20 female, 13 male) individuals with eating disorders were documented in our matched cohort.…”
Section: Discussioncontrasting
confidence: 65%
“…Another aspect that must be kept in mind is that eating disorders are related to fractures in adolescents, especially in girls, and T1D is known to be associated with disturbed eating behavior. (39,40) Even in our cohort, the proportion with fractures, with versus without eating disorders, was 60 (38 to 79) % versus 16 (14 to 18) %, p < 0.001 in females, whereas no significant difference could be found in males (31 [12 to 59] % versus 17 [15 to 18] %, p = 0.183). However, these results should be interpreted with caution as only 33 (20 female, 13 male) individuals with eating disorders were documented in our matched cohort.…”
Section: Discussioncontrasting
confidence: 65%
“…A recent cohort study of 344 female patients who were being treated for eating disorder found a significantly lower BMD at the L-spine (16%), femoral neck (18%), and total hip (23%) in patients with active AN. Patients in remission had lower BMD than healthy controls but higher than women with active AN at the L-spine and hip [62].…”
Section: Bone Health In Anorexia Nervosamentioning
confidence: 78%
“…A recent study that demonstrated increased fracture risk in AN did not find a direct association with decreased BMD [62]. Authors cited potential limitations of DEXA for assessing BMD in patients with AN, including relationships between DEXA and fracture risk taken primarily from post-menopausal populations, altered body composition arising from cycles of weight-loss and weight-gain leading to inaccurate estimate of BMD, and difficulty estimating the cumulative effects of AN given multiple periods of disease relapse and remission [62]. Further studies need to be conducted to better elucidate how to utilize DEXA in evaluating and reducing fracture risk in patients with AN.…”
Section: Bone Health In Anorexia Nervosamentioning
confidence: 84%
See 1 more Smart Citation
“…Fracture risk is increased in women with AN across all ages and at all skeletal sites, whereas increased fracture risk in men with AN is seen after age 40 years [ 100 ]. A cross-sectional study in adolescent girls with active AN and an eight-year longitudinal study in adults with AN (regardless of current disease status) did not find an association between BMD by DXA and prevalent or incident fractures, respectively [ 101 , 102 ]. This may be because (1) the study populations were heterogeneous in terms of duration of disease and disease status, (2) known relationships between BMD and fracture risk are derived from a different population (i.e., post-menopausal women), (3) DXA may not be as accurate at the extremes of the weight spectrum, and (4) DXA does not capture detrimental changes to bone microarchitecture and bone matrix properties that are important determinants of bone strength.…”
Section: Skeletal Integritymentioning
confidence: 99%